PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF STUDENT PREPARATION FOR PEDAGOGICAL ACTIVITY - Badalov Kamoliddin Rahmat o‘g‘li (PEDAGOGS, 2023)
Abstract: Opinions about the psychological-pedagogical aspects of preparing students for pedagogical activity are given. Conclusions are drawn.